Analisis Perbandingan Pendapatan Petani Sebelum dan Sesudah Alih Fungsi Lahan Padi Sawah di Kecamatan Panyabungan Barat - Amelia Zahra Yusnar; Rahmat Suryanto Pirngadi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The conversion of agricultural rice farming land happens continuously in Panyabungan Barat Sub-District, Mandailing Natal District, where in the last five years, it was recorded that 404 Hectares of paddy field were lost due to land conversion. Apart from expanding settlements, papaya cultivation is the most significant factor in converting paddy fields at Panyabungan Barat Sub-District. This research aimed to compare the incomes of wet-rice farmers before and after the conversion of wet-rice land in the Panyabungan Barat sub-district. The analytical method in this study uses income analyses. The research results found that farmers' income before land conversion was IDR12,627,000/Ha/planting season, and after land conversion, farmers earned an income of IDR361,500,500/Ha/planting season. If the farmer's income is converted in terms of months, then before the land conversion, farmers earn an income of IDR2,104,000/month, while after the land conversion, farmers earn an income of IDR10,041,680 / Ha/month.